Towards a more accountable G20? Accountability mechanisms of the G20 and the new challenges posed to them by the 2030 Agenda - Sören Hilbrich; Jakob Schwab (Deutsches Institut für Entwicklungspolitik (DIE), 2018)
Many measures customarily employed within states to provide checks to and surveillance of the exercise of power, such as public elections, are not available with regard to the political institutions of global governance. For this reason, the accountability of such institutions is frequently a subject of particular discussion. A key institution in global governance whose legitimacy is constantly being challenged is the Group of 20 (G20). In this paper, we analyse the existing mechanisms pertaining to the accountability of the G20 and discuss the challenges that the new role of the G20 with regard to the 2030 Agenda for Sustainable Development poses to them. To do so, we develop a concept of accountability which is applicable to the G20 as an institution of global governance. According to this concept, accountability consists of three elements: transparency, justification, and the possibility of sanctions in response to the activities of the institution. In addition, many accountability mechanisms fulfil an additional function with respect to the internal learning of an institution from past experiences. Based on this conceptualisation of accountability, we identify interaction with the media, the publication of accountability reports, and the interaction process with Engagement Groups from business, academia, and civil society as the most important accountability mechanisms of the G20. These mechanisms differ with regard to their primary addressees as well as with regard to the elements of accountability they are contributing to. In order to increase the accountability of the G20, several suggestions can be made, particularly in light of the demands set by its new role in the implementation of the 2030 Agenda. To increase the effectiveness and credibility of its accountability processes, the G20 should facilitate a more independent evaluation of its activities such as by its Engagement Groups or through public discussion. For this to become possible, the work of the G20 must first and foremost become more transparent. Possible ways of achieving this range from the establishment of a permanent website, over the allowing of selected civil society members to attend its working group meetings, to publishing agendas and minutes. Self-reports should concentrate on descriptions rather than evaluations and should cover G20 policies relevant to the implementation of the 2030 Agenda coherently. Such improvements in the existing system of accountability mechanisms cannot fully compensate for the shortcomings – also with regard to accountability – that are related to the limited membership of the G20. Nevertheless, they would constitute important steps forward towards a more accountable G20.
Keywords: 330; Agenda 2030